PERKEMBANGAN TANGGUNG JAWAB PEMEGANG SAHAM PERSEOAN TERBATAS DALAM UNDANG-UNDANG NASIONAL MENGGANTIKAN HUKUM WARISAN KOLONIAL - Rohendi, Acep (Yustitia, 2018)
Law No. 40 of 2007 concerning Limited Liability Companies (UUPT) revokes Law Number 1 Year 1995 concerning Limited Liability Companies (UUPTL). This UUPTL replaces the provisions of a limited liability company inherited from the Dutch East Indies contained in the Commercial Code (KUHD) stipulated in the Third Section concerning Limited Liability Companies starting from Article 36 to Article 56 KUHD. The shareholders who are regulated in the UUPTL and the KHUD are not personally responsible for the agreements made on behalf of the Company and are also not responsible for the Company's losses in excess of the value of the shares they have. The KUHD also states that shareholders are not responsible for more than the full amount of their shares. Its development after being determined by the Company Law in 2007, the responsibility of the shareholders is not absolutely valid. The liability is unlimited and personal responsibility is fully imposed on the shareholders of the limited company in the 2007 Company Law. If the shareholders of a limited company violate or fulfill the elements stipulated in Article 3 paragraph (2) of the Company Law, or known as the Piercing The Corporate Veil principle (disclosure of the company's veil). This development is a sanction to shareholders of a limited liability company, which in the previous provision was unknown.